Nilai Pendidikan Karakter Dalam Kesenian Dusun Lantaboko - Dzulfitra Ramadani Mar; Asia Ramli; Nurlina Sjahrir (VisArt: Jurnal Seni Rupa dan Design, 2025)
This study aims to describe and analyze the representation of character education values in traditional art performances in Dusun Lantaboko, Bontokassi Village, Parangloe District, Gowa Regency. The art form examined is gambus music, which, as one of the traditional arts of the Makassar community, serves a broader function than mere entertainment. It acts as a medium for conveying moral messages, a space for social interaction, and a means of character formation rooted in local wisdom. This study employs a descriptive qualitative approach, with data collected through participatory observation, in-depth interviews with gambus performers and community leaders, and documentation of performances. The findings reveal that gambus art in Dusun Lantaboko embodies four main representations of character education values: (1) honesty, reflected in the spontaneity of the lyrics, openness of expression, and alignment of moral messages with social realities; (2) responsibility, manifested in the performers’ commitment to preserving the tradition, discipline in performance, and the community’s awareness of its collective role in cultural preservation; (3) creativity, evident in lyrical improvisation, originality of ideas, and the use of simple artistic tools as supporting instruments; and (4) mutual cooperation, expressed through community collaboration in preparing performances, voluntary social participation, and collective, non-formal patterns of cultural transmission